Wear Behavior of Cu-Cr-Zr Alloy under Electric Current - Turhan, Hueseyin; Goekcen, Cigdem (Carl Hanser Verlag, 2009)
A Cu-Cr-Zr alloy (Alloy C 18150) was investigated for tribological behavior in the presence of electric current flow. Experiments involving adhesive wear were conducted under atmospheric conditions at a constant load of approximately 40 N over a duration of 30 minutes, at three different current values (1 A, 2.5 A and 10 A) and two different DC polarities (+/-), and at three different rotational speeds (1 m/s, 2 m/s and 4.2 m/s). Weight loss measurements were noted and wear behavior was evaluated using surface analysis including SEM and EDS. It was observed that friction speed and its related temperature affected the material loss. It has been considered that the compounds Cr2O3 and Cr2Zr, which form at the surface for positive and negative current flow, respectively, are responsible for this material loss. The wear behavior demonstrated favorable results with current, with wear resistance increasing at higher current intensity, regardless of polarity.
Keywords: Surface